Perbandingan Pengujian Kandungan Aspal: Metode Centrifuge vs Reflux - Fitri, Insira insani; Zebua, Delfi Kurnia; Febiola, Ollga (Jurnal Kridatama Sains dan Teknologi, 2025)
This study aims to compare asphalt content testing results using the centrifuge method and the Reflux method on Asphalt Concrete-Binder Course (AC-BC) mixtures. The research was conducted experimentally using samples collected from an Asphalt Mixing Plant (AMP) in Kerinci Regency. The results show that the Reflux method produced an average asphalt content of 6.059%, which is more accurate and closer to the actual asphalt content compared to the centrifuge method with an average of 5.986%. The differences are attributed to the precision level of the equipment and the testing processes. Although the centrifuge method is faster, its results are less consistent compared to the Reflux method. Factors such as human error and equipment conditions also influenced the test outcomes. The Reflux method is recommended for tests requiring high accuracy, despite its longer testing duration and higher potential risks. This study is expected to serve as a reference for quality control of asphalt mixtures in laboratories and fieldwork